System-on-a-chip test-data compression and decompression architectures based on Golomb codes. - Chandra, A. (IEEE Transactions on computer-aided design of integrated circuits and systems)
We present a new test-data compression method and decompression architecture based on variable-to-variable-length Golomb codes. The proposed method is especially suitable for encoding precomputed test sets for embedded cores in a system-on-a-chip (SoC). The major advantages of Golomb coding of test data include very high compression, analytically predictable compression results, and a low-cost and scalable on-chip decoder. In addition, the novel interleaving decompression architecture allows multiple cores in an SoC to be tested concurrently using a single automatic test equipment input-output channel. We demonstrate the effectiveness of the proposed approach by applying it to the International Symposium on Circuits and Systems' benchmark circuits and to two industrial production circuits. We also use analytical and experimental means to highlight the superiority of Golomb codes over run-length codes